A green ultra-lightweight chemically foamed concrete for building exterior: A feasibility study. (15th March 2021) - Shi, Jinyan; Liu, Baoju; He, Zhihai; Liu, Yuanchun; Jiang, Junyi; Xiong, Tianyu; Shi, Jiawei
Abstract: Ultra-lightweight foamed alkali-activated concrete based on river sediment-metakaolin blends was prepared by the mixed foaming method of chemical foaming. Polluted river sediment is transformed into eco-friendly foamed concrete without heating and pressure. The results showed that ultra-lightweight foamed concrete presented its dry density between 100 and 600 kg/m 3, the thermal conductivity between 0.0376 and 0.1800 W/(m∙K), and the compressive strength between 2.23 and 5.70 MPa, showing better mechanical and thermal performance than the traditional Portland foamed concrete with the similar density. In addition, river sediment-based foamed concrete mixed with expanded polystyrene particles has good high temperature resistance and water resistance, as well as excellent thermal insulation performance under high temperature and high humidity conditions. This study has verified the feasibility of river sediment for the preparation of green foamed concrete from various aspects, which can not only consume a large amount of polluted river sediment, but also obtain good economic benefits and a low leaching rate of heavy metals. Graphical abstract: Image 1